Predictors of poor quality of life for patients discharged from acute psychiatric care in Alberta - Owusu, Ernest; Mao, Wanying; Shalaby, Reham; Elgendy, Hossam Eldin; Agyapong, Belinda; Eboreime, Ejemai; Lawal, Mobolaji A.; Nkire, Nnamdi; Silverstone, Peter H.; Chue, Pierre; Li, Xin-Min; Vuong, Wesley; et al. (Frontiers in Psychiatry, 2025)
BackgroundQuality of life (Qol) is a multi-dimensional concept composed of various dimensions, including mental and/or psychological well-being and physical and/or biological health. Objective: The objective of this study is to assess the prevalence and predictors of poor Qol outcomes across the five dimensions of the EQ-5D-5L, namely, mobility, self-care, usual activities, pain/discomfort, and depression/anxiety for individuals discharged from acute psychiatric care in Alberta.MethodsMultiple binary logistic regression models were performed to examine the association between sociodemographic variables and EQ-5D-5L dimensions.ResultsOut of the 1106 participants, the majority were Caucasian, 61.6%, 25 years or less, 36.4%, females 54.8%, and had a high school diploma, 51.4%. The prevalence of depression/anxiety in the cohort is 89.2%. Caucasians were two times more likely to present with problems regarding pain/discomfort (OR=2.14; 95% C.I. 1.39 - 3.27) compared to Black participants. Also, retired participants were three times more likely to present with pain/discomfort (OR 3.18; 95% C.I. = 1.45 - 6.96) than those employed. Finally, participants with likely anxiety were almost two times more likely to present problems relating to self-care (OR=1.99; 95% C.I. = 1.41 - 2.81) compared with those who had unlikely anxiety.ConclusionThis study’s results highlight the complex interplay of demographic, socioeconomic, and mental health factors that influence various health-related problems. These findings underscore the importance of targeted, holistic health interventions that address physical and mental health needs.